Achieving a high-strength binary Mg–15Gd alloy by nano substructure with Gd segregation and nano clusters1. Issue 10 (3rd October 2022) - Li, R.G.; Yan, Y.; Pan, H.C.; Zhang, H.; Li, J.R.; Qin, G.W.; Liu, B.S.
Abstract : A high-strength binary Mg–15Gd alloy plate, prepared by the conventional extrusion, warm-rolling and aging, exhibits an excellent mechanical property with 504, 518 MPa and 4.5% for yield strength, ultimate tensile strength and elongation, which is mainly attributed to the nano substructure with boundary segregation of Gd atoms, the high-density nano clusters induced by dislocations in the interior of grains, the high-density dynamical precipitates with submicron size, and the strong basal texture. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A new strengthening mechanism involving the nano substructure with Gd segregation, high-density nano Gd clusters induced by dislocations, and high-density dynamical precipitates has been found in Mg–Gd binary alloys.